Methods for Film Synthesis and Coating Procedures - Nánai, László; Samantara, Aneeya; Fábián, László; Ratha, Satyajit (IntechOpen, 2020)
In recent years, thin layer technologies, including fabrication of different micro- and nano-structures, have undergone tremendous progress. Such layers are made for a variety of industrial and scientific applications. Due to the extreme physico-chemical properties of the available structures, there are many promising applications (eg, due to biocompatibility, biological and medical applications between living tissues and materials). Pre-tailored special surface layers/structures could be realized for implants in dental, neurological and orthopedic applications. There are also different methods that have been applied to produce special mono and multilayers with extreme electrical end magnetic properties. Also some methods have been developed to produce surface structure applications eg, for environmental applications with necessary resistivity and anti-corrosion properties.Some theoretical/mathematical simulation methods have also been developed for better compatibility of theory with experiments.This book consists of 10 chapters describing the physico-chemical base of deposition and coating microfabrication, thus providing some overview on how to measure the physical and chemical parameters of fabricated structures and how to solve compatibility and fitting problems, etc.